52.2k views
1 vote
Solve the following equation.
(3y - 2)/3 + (2y + 3)/2 = y + 7/6​

2 Answers

5 votes
Answer:
y=1/3

Step-by-step explanation:
steps:
multiply each side by 6 (the fraction and y)
1. 2(3y-2)+3(2y+3)=6y+7

work problems in parentheses
2. 6y-4+6y+9=6y+7

combine like terms
3. -4+6y+9=7

4. 5+6y=7

5. 6y=7-5

6. 6y=2

7. y=2/6 =1/3
User Edwina
by
5.8k points
1 vote
y= 1/3 see the attachment for solution
Solve the following equation. (3y - 2)/3 + (2y + 3)/2 = y + 7/6​-example-1
User Wrokar
by
5.4k points